BLOCK CHAIN WITH SECURITY ANALYSIS PERFORMANCE IMPROVEMENTS IN LIGHTWEIGHT ACCESS CONTROL FOR EHRS SHARING (International Journal of Food and Nutritional Sciences, 2023)
Recent years have witnessed a paradigm shift in storage of Electronic Health Records (EHRs) on mobile cloud environments where mobile devices are integrated with cloud computing to facilitate medical data exchanges among patients and healthcare providers. This advanced model enables healthcare services with low operational cost, high flexibility and EHRs availability. However, this new paradigm also raises concerns about data privacy and network security for e-health systems.. In this paper, we propose a novel EHRs sharing framework that combines blockchain and the decentralized interplanetary file system (IPFS) on a mobile cloud platform. Particularly, we design a trustworthy access control mechanism using smart contracts to achieve secure EHRs sharing among different patients and medical providers